Modeling of photon trapping effects in high-density divertor plasmas. (May 2020) - Rosato, J.; Koubiti, M.; Marandet, Y.; Stamm, R.
Highlights: The trapping of atomic line radiation in high-density divertor plasmas is examined. The mechanisms underlying line broadening, such as Doppler and Stark effects, are shown to strongly affect the photoexcitation rate. Monte Carlo simulations of the radiation transport in slab geometry are performed as an illustration. Abstract: In divertor plasmas at high density regimes, typically with Ne larger than 10 14 cm − 3, the photons emitted in the resonance line of the hydrogen isotopes have a mean free path that can be as short as one millimeter. They provide an additional source of excited atoms, which can be ionized more easily; a consequence of this is that the whole ionization-recombination balance of the divertor plasma can be altered. In this work, we investigate the influence of the spectral line profile on the photoexcitation rate. A kinetic Monte Carlo solver is applied to the transport of photons in slab geometry. The relative contribution of the Doppler and Zeeman effects on the line profile is examined. In the framework of ITER nuclear phase preparation, we also examine the influence of deuterium and tritium line shape overlapping and we address the transport of the helium resonance line radiation.